PENGARUH VARIABEL KEUANGAN DAN NON KEUANGAN TERHADAP UNDERPRICING SAHAM PADA SAAT IPO DI BURSA EFEK INDONESIA (PERIODE 2021-2023) - Paris Pebrian Sirait; Agung Juliarto (Diponegoro Journal of Accounting, 2026)
The phenomenon of underpricing remains a dominant characteristic in Initial Public Offerings (IPOs) in the Indonesian capital market. Underpricing occurs when the offering price in the primary market is lower than the closing price on the first trading day in the secondary market. While this condition benefits short-term investors, it may disadvantage issuers due to suboptimal capital raised. This study aims to examine the influence of financial and non-financial factors on the level of IPO underpricing on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The independent variables include Return on Assets (ROA), Debt to Equity Ratio (DER), firm size, and auditor reputation, with underpricing as the dependent variable. This research employs a quantitative approach using multiple linear regression analysis on non-financial companies that conducted IPOs during the observation period. The results indicate that ROA, DER, firm size, and auditor reputation simultaneously affect the level of underpricing. Partially, ROA and firm size have a negative effect on underpricing, DER has a positive effect, while auditor reputation shows a negative but not consistently significant effect. These findings suggest that both financial fundamentals and non-financial signals play an important role in determining IPO pricing in the Indonesian capital market.